A new flavonol acylglycoside from the fruits of Nitraria tangutorum Bobr. Issue 21 (2nd November 2021) - Jiang, Sirong; Zhang, Yupei; Zhao, Xiaohui; Shao, Yun; Wei, Wei; Tao, Yanduo; Yue, Huilan
Abstract: Phytochemical investigation on the ethanol extract of the fruits of Nitraria tangutorum Bobr. led to the isolation of a new flavonol acylglycoside tangutoside (7 ) and six known ones including p -formylphenol (1 ), 3-formylindole (2 ), rutin (3 ), prionitisid B (4 ), quercitrin (5 ) and flazin (6 ). Among them, compounds 2, 4, and 5 were isolated from Nitraria tangutorum Bobr. for the first time. Their structures were identified by spectroscopic methods and by comparison with data reported in the references. The compounds 3, 4, 5, and 7 were demonstrated to possess strong DPPH radical scavenging ability with IC50 values of 31.45 μg/mL, 19.21 μg/mL, 59.30 μg/mL, and 44.54 μg/mL, respectively. Graphical Abstract: